Sleepwalkers [videorecording (DVD)] - Krause, Brian, 1969-; Amick, Mädchen; Krige, Alice, 1954-; Garris, Mick; King, Stephen, 1947- (Columbia TriStar Home Video, 2000)
A sexually curious virgin falls for the new boy in school, only to learn too late he's a life-sucking Sleepwalker.